In vivo assessment of Immune Response to Pseudomonas aeuroginosa antigens - Rasha Hadi Saleh, et.al (Al-Qadisiyah Journal of Pure Science, 2017)
Intrduction: The study of immunogenicity of pseudomonal antigens is essential for both diagnosis and prevention for Pseudomonas aeruginosa infections.Aims: This study is aimed to investigate the immunogenicity of Pseudomonal antigens in experimental animals.Materials and methods: Outer membrane proteins (OMPs) and Lipopolysaccharaid (LPS) were used as antigens and administrated into lab animals via I.V. and I.P route. The immune response was assessed depending on the titer of anti-pseudomonal-antibody and phagocytic index.Results: The mean of anti-LPS antibody titer injected via Intraperitoneally I.P and I.V intravenous route were 80 and160 respectively, while the mean of anti -OMP antibody titer injected via I.P and I.V route were 320 and 1280 respectively as compared with antibody titer for control (non-immunized rabbits) which was 20. Besides, it was found that OMPs stimulate cellular immune response, since there was significant increasing in phagocytic index(P< 0.05) in rabbits that injected with OMPs via both I.P and I.V (12% and 13%) respectively as compared with control animals(9%), while there are no significant increase in phagocytic index (PËƒ0.05) in rabbits that injected with LPS via both I.P and I.V (8%) and(6%) respectively as compared with control animals (9%).Conclusion: OMPs were found to be good immunogen, since it was able to induce both types of immune response humoral and cellular, While Lipopolysaccharaid (LPS) induced only humoral immunity